Growth and Quality of Zinnia elegans L. in Response to Different Growth Stimulants: Growth and Quality of Zinnia elegans L. (Biological Sciences - PJSIR, 2024)
Zinnia elegans L. is a cut flower, to improve the growth parameters of this flower salicylic acid (SA) and calcium chloride (CaCl2) can act as growth stimulants. The purpose of this study was to assess the effects of pre-harvest SA and CaCl2 treatments in extending the vase life, quality and quantity of cut Zinnia flowers. Therefore, completely randomized design was made with SA at the rate of 0.5 mg/L,      1 mg/L and 1.5 mg/L and CaCl2 at the rate of 0.5 mg/L, 1 mg/L and 1.5 mg/L with 3 replicates in each treatment. Changes in growth morphology (such as shoot length, root length, dry weigh of root and plant, fresh weight of root and plant, total number of flowers and total number of flower cluster per plant), Physiology (chlorophyll content, PPO activity and protein) and phosphorous and potassium concentration were checked. The research study led to following conclusions that the foliar application of calcium chloride @ 1.5 mg/L + salicylic acid @ 0.5 mg/L resulted in highest growth parameters of Zinnia. The quality parameters like chlorophyll, total protein, phosphorous and catalase content also showed maximum value during the course of the study. It can be concluded in nutshell that calcium chloride in combination with salicylic acid results in better growth and quality of zinnia under the agro-climatic conditions of Lahore. These results suggest that SA and CaCl2 could be used as potential growth promoters to improve quantity and quality of Zinnia elegans L.